Cognitive Interpretation Of The Phenomenon Of Metonymy - Shodikulova Aziza Zikiryaevna (Genius Journals, 2022)
Following structural linguistics, considering metonymy as a figure of meaning based on a contiguity relationship, lexical semantics considers metonymy as a mechanism for expanding lexical meaning. Cognitive linguistics regards metonymy as a way of thinking and a cognitive process based on conceptual contiguity. Metonymy in cognitive linguistics is considered a conceptual phenomenon that structures and shapes of human thinking and language. This tool is also considered ubiquitous in the language and has cognitive and communication functions
Keywords: metonymy; phenomenon; cognitive; illocution